Circular RNA vaccines: Pioneering the next-gen cancer immunotherapy - Uddalak Das; Soupayan Banerjee; Meghna Sarkar; Fathah Muhammad L; Tanveen Kaur Soni; Madhumita Saha; Gayatri Pradhan; Bhaskarjyaa Chatterjee (Cancer Pathogenesis and Therapy)
Circular ribonucleic acid (circRNA) vaccines have emerged as a revolutionary strategy in cancer immunotherapy, facilitating novel approaches to induce robust and durable immune responses. Unlike traditional linear messenger RNA (mRNA) vaccines, circRNAs exhibit exceptional stability, enhanced translational efficiency, and resistance to exonuclease degradation, making them ideal candidates for vaccine development. This review delved into the fundamental principles underlying circRNA biology, highlighting their unique structural advantages and translational potential. We examined recent advancements in circRNA vaccine design, focusing on their application in oncology. As the circRNA-based cancer vaccine is a relatively novel technology, findings from all the major studies describing its efficacy were discussed. We further investigated their combination with other immunotherapeutic modalities, such as immune checkpoint inhibitors and adoptive cell therapies, that ensure the maximal anticancer effects of circRNA vaccines. Large-scale manufacturing, immunogenicity optimization, delivery systems, and other challenges and future directions in this field were also discussed. This study aims to thoroughly analyze the state-of-the-art and potential future applications of circRNA vaccines in cancer immunotherapy, highlighting them as exciting possibilities for next-generation cancer therapies.